Engineering Carbon-Semiconductor Hybrid Materials for Photocatalysis and Solar Cells - Shen, Zhangfeng (Curtin University, 2017)
Carbon-semiconductor hybrid materials (CSHMs) are promising candidates for solar energy conversion because of their enhanced light harvesting ability and the prolonged charge carrier separation. In this thesis, a series of CSHMs has been successfully fabricated and applied in photocatalysis and dye-sensitized solar cells. The aim of this thesis is to develop cost-effective methods to prepare CSHMs with appropriate morphologies, compositions, and interfacial contact to promote the efficiency of photocatalysis and solar energy conversion.